Host-guest interactions and confinement effects in HZSM-5 and chabazite zeolites studied by low-field NMR spin relaxation. (June 2022) - D'Agostino, C.; York, A.P.E.; Bräuer, P.
Abstract: The characterization of fluid/solid interactions in porous materials is crucial for their design and optimization, most notably in applications such as adsorption and catalysis. Yet, probing interfacial phenomena of fluids confined in porous systems is particularly challenging. Nuclear magnetic resonance (NMR) spin relaxation has emerged in recent years as a rapid, non-invasive experimental technique to probe adsorbate/adsorbent interactions in mesoporous catalytic materials. More recently, NMR relaxation measurements performed on high-field (300 MHz) superconducting magnets have been successfully validated as a robust method to characterize acidity in HZSM-5 zeolites. Expanding such techniques in the context of low-field, bench-top NMR instruments would be highly beneficial as it would make NMR relaxation a much more appealing and accessible tool for non-invasive, rapid characterization of adsorbate/adsorbent interactions in zeolites and microporous materials. Herein, we validate the use of low-field, bench-top NMR spin relaxation as an indicator for characterizing host-guest interactions in microporous zeolitic materials, using water as guest molecules confined within two different zeolite frameworks, HZSM-5 and chabazite, with varying silica/alumina ratio. The results reported here demonstrate the robustness and sensitivity of low-field NMR relaxation measurements as a rapid screening tool for characterizing adsorption and molecular dynamics in microporous materials, with important implications for both academics and industrialists in terms of making the method more widely accessible, hence expanding the set of tools for materials chemistry and characterization. Graphical abstract: Image 1 Highlights: Low-field nuclear magnetic resonance (NMR) spin relaxation is used to characterize interactions in zeolites. The behavior of water confined in HZSM-5 and chabazite at different silica/alumina ratio is studied. The T 1 / T 2 ratio is a robust indicator of the host-guest surface interactions. Increase in zeolite acidity (lower silica/alumina ratio) leads to higher T 1 / T 2 values. Confinement effects need to be considered for zeolites with different pore size.